2012
DOI: 10.1073/pnas.1118754109
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin signaling initiates the activation of astrocytes and its dysregulation contributes to the pathogenesis of astrocytomas

Abstract: Astrocytes are the most abundant cell of the CNS and demonstrate contact inhibition in which a nonproliferative, nonmotile cellular state is achieved once stable intercellular contacts are formed between mature cells. Cellular injury disrupts these intercellular contacts, causing a loss of contact inhibition and the rapid initiation of healing. Dysregulation of the molecular pathways involved in this process is thought to lead to an aggressive cellular state associated with neoplasia. We investigated whether a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 41 publications
3
60
0
Order By: Relevance
“…Mechanically, the interplay between GRβ and β-catenin was demonstrated to be a necessary component of astrocyte reactivity through sustained Wnt/β-catenin/TCF signaling in its dominant-negative effect on GRα mediated trans-repression by a GSK-3β-independent manner. Several reports have shown that aberrant activation of Wnt/β-catenin/TCF signaling is an important contributing factor in glioma development (Ref) [11][12][13]. Our previous finding that GRβ is predominately distributed in the nucleus and contributes to glioma pathogenesis raises the consideration that the cross-talk between GRβ and β-catenin/TCF signaling involves in the progression of glioma [9].…”
Section: Introductionmentioning
confidence: 96%
“…Mechanically, the interplay between GRβ and β-catenin was demonstrated to be a necessary component of astrocyte reactivity through sustained Wnt/β-catenin/TCF signaling in its dominant-negative effect on GRα mediated trans-repression by a GSK-3β-independent manner. Several reports have shown that aberrant activation of Wnt/β-catenin/TCF signaling is an important contributing factor in glioma development (Ref) [11][12][13]. Our previous finding that GRβ is predominately distributed in the nucleus and contributes to glioma pathogenesis raises the consideration that the cross-talk between GRβ and β-catenin/TCF signaling involves in the progression of glioma [9].…”
Section: Introductionmentioning
confidence: 96%
“…The genes activated by β-catenin signaling are regulatory and often lead to proliferation and migration [11,163]. Interestingly, Yang et al (2012) found this contact initiated activation of astrocytes to parallel what occurs in the transformation of astrocytomas, further coupling the process of astrocyte activation and tumor progression [162].…”
Section: Reactive Astrogliosismentioning
confidence: 99%
“…Therefore, mechanical disruption occurs when processes such as migration and/or proliferation of surrounding cells is initiated. Such mechanical signals could come potentially emerge from tumor cells, subsequently triggering astrocyte activation via disruption of these cell surface complexes such as cadherins and β-catenin [161,162]. The genes activated by β-catenin signaling are regulatory and often lead to proliferation and migration [11,163].…”
Section: Reactive Astrogliosismentioning
confidence: 99%
“…21 The previous observations hinged on the fact that PTN was able to induce dimerization of PTPRZ and that this change of oligomeric state inactivated the intracellular phosphatase activity. A model implicating the dimerization/inhibition of RPTPs has been favored since the crystal structure of a dimeric form of the D1 domain of PTPRA was determined and showed that a helixturn-helix motif (called a wedge) of one protomer was inserted into the active site of a second protomer and blocked its active site.…”
mentioning
confidence: 99%
“…18 Critically, alterations in the assembly of cadherin-catenin adhesion complexes are linked to the disassociation of adherent epithelial cells and their subsequent migration, a process that can be part of the normal aspect of tissue development, but is also a hallmark of cancer growth and metastasis 18,19 (the effects of E-and N-cadherin in cancer progression and epithelial-mesenchymal transitions are discussed by LeBras, Taubenslag and Andl in this issue). These transitions can be brought about by enhanced tyrosine phosphorylation of β-catenin, 20,21 which explains why the association of type IIb RPTPs with components of cadherin-catenin adhesion complexes has been of particular interest. [22][23][24][25][26][27][28] For example, PTPRM associates with E-cadherin 23 and dephosphorylates p120 catenin.…”
mentioning
confidence: 99%